ANALYSIS AND MANUFACTURING OF CHILDREN PLAYING TOOL IN KINDERGARTEN SCHOOL - Wiyogo; Galfri Siswandi (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
The making of children's play equipment is in the form of a set of tools where the playground has the benefits of training early childhood motor skills. The implementation of the activity was carried out in the Kindergarten Pembina Jekan Raya District, Palangka Raya as a partner. The purpose of community service activities carried out in tertiary institutions is in line with the functions and objectives mandated in Law Number 12 of 2012, Article 4 paragraph 3;